O problema de sequenciamento de caminhões emum centro de crossdocking com duas máquinas - Gabriela Braga Fonseca (2015)
Scheduling is a decision-making process that is used on a regular basis in many ma nufacturing and services industries. It deals with the allocation of resources to tasks over given time periods and its goal is to optimize one or more objectives. This work aims to develop effective ways to solve the truck scheduling problem at a cros sdocking facility, denoted by F 2 CD Cmax and formulated as a scheduling problemof flowshop type with two-machines with crossdocking constraints, in which the ob jective function seeks to minimize the makespan (Cmax). For this, an integer linear programming model based in a time-indexed formulation is considered. To confirm and evaluate the solutions tests with 500 instances were performed. We implemented the Lagrangian Relaxation by Volume Algorithm, in order to obtain good solutionsin time computationally efficient. Furthermore four polynomial heuristics have been proposed and analyzed in order to find an upper bound for problem. The results demonstrate the efficiency of lagrangean relaxation and implemented heuristics.